EVALUASI STRATEGI BERSAING PT. BANK NEGARA INDONESIA (PERSERO), TBK., DALAM MEMBERIKAN KREDIT KEPADA UNIT MIKRO, KECIL DAN MENENGAH - , Elke Florence Getsy Meliala; , Dr. Bambang Riyanto, LS., MBA., ([Yogyakarta] : Universitas Gadjah Mada, 2012)
A company strategy is the plan of management is using to stake out a market position, conduct its operations, attract and please customers, compete successfully, and achieve organizational objectives. A strategy thus entails managerial choices among alternatives and signal organizational commitment to specific markets, competitive approaches, and ways of operating. One of objectives of strategy is providing better guidance to the entire organization members more alert to environmental changes and the competition situation. The management should compose their competitive strategy for consolidating the market and crafting their core competences. These thesis focuses on describing banking industry, specially preferred on micro, small and medium enterprise (MSME) lending program. Now a days, the growth of MSME lending program by several opportunities such as the MSME in national economy have an important and strategic roles and become the pillars of national economy. MSME has proven tough , although the economic crisis still affecting the whole industry. The result is, banking industry try to change their strategy by choosing the MSME as the bigger portfolio than the corporate portfolio. It also happened at PT. Bank Negara Indonesia (Persero), Tbk., (BNI). BNI tried to increase the share in giving lending to this sector because the profit of lending in this sector is maximize but the risk is minimize. Eventhough BNI has tried to make strategy, but if it compared to banking industry, the growth is still under the expectation. This research objectives are to identified external and internal factors which has positive influence regarding the bank, and try to find the fit alternatives strategies, and the last is to propose the best strategy to be choose by BNI for considering the execute the opportunities in giving lending to MSME. The research instrument to be used are Industry Characteristics, Porterâs Five Forces Model, Driving Forces and Key Success Factors. The research resulting that to compete successfully, BNI with itâs strategic business unit Divisi USK should execute some strategies that are strategy of product, strategy pricing, process and reengineering the organizational structure.